2022
DOI: 10.3390/coatings12111643
|View full text |Cite
|
Sign up to set email alerts
|

Whether Carbon Nanotubes Are Capable, Promising, and Safe for Their Application in Nervous System Regeneration. Some Critical Remarks and Research Strategies

Abstract: Carbon nanotubes are applied in or considered for different fields of medicine. Among them is the regeneration or rebuilding of nervous system components, which still lack substantial progress; this field is supported by carbon nanotubes to a great extent as the principal material. The limited research on this issue has involved PU/silk/MWCNTs, PCL/silk/MWCNTs, PCL/PGS/CNTs, chitin/CNTs, PGF/CNTs, CNTs/PGFs/PLDLA, MWCNTs/chitosan, MWCNTs/PPy, PLA/MWCNTs, PU/PAA/MWCNts, GelMA/SACNTs, and CNTs alone, which have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 172 publications
0
4
0
Order By: Relevance
“…Pure carbon NPs constitute the largest and most important group of nmNPs, whic include nanotubes, nanohorns, nano-onions, nanodiamonds, fullerenes and graphene and exhibit large diversity in structure, morphology, physical properties and chemica reactivity [1,[12][13][14][15]. Another carbon-containing, large group of nmNPs are dendrimers These NPs have a highly branched three-dimensional structure, consisting of an initia core, several internal layers, repetitive units and several terminal active surface groups The presence of a hydrophobic core and multiple surface groups makes them a good candidate for high-load drug carriers [1,16,17].…”
Section: Non-metallic Npsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pure carbon NPs constitute the largest and most important group of nmNPs, whic include nanotubes, nanohorns, nano-onions, nanodiamonds, fullerenes and graphene and exhibit large diversity in structure, morphology, physical properties and chemica reactivity [1,[12][13][14][15]. Another carbon-containing, large group of nmNPs are dendrimers These NPs have a highly branched three-dimensional structure, consisting of an initia core, several internal layers, repetitive units and several terminal active surface groups The presence of a hydrophobic core and multiple surface groups makes them a good candidate for high-load drug carriers [1,16,17].…”
Section: Non-metallic Npsmentioning
confidence: 99%
“…Pure carbon NPs constitute the largest and most important group of nmNPs, which include nanotubes, nanohorns, nano-onions, nanodiamonds, fullerenes and graphene, and exhibit large diversity in structure, morphology, physical properties and chemical reactivity [1,[12][13][14][15]. Another carbon-containing, large group of nmNPs are dendrimers.…”
Section: Non-metallic Npsmentioning
confidence: 99%
“…Kakarla et al [8] used the representative volume elements (RVE) method and FEA to study the maximum stress distributions and mechanical properties of boron nitride nanotubes (BNNTs)reinforced gelatin (G) and alginate (A) hydrogel. Also, efforts have been made using matrices PLA and PCL with fillers like multiwall carbon nanotubes (MWCNTs), chitosan (CS) and silk [14][15][16][17]. It has been found recently that PCL/CS/CNT composite matches well with the heart's electrical conductivity [16].…”
Section: Introductionmentioning
confidence: 99%
“…Olivares et al used also FEA method to study the mechanical and fluid properties in gyroid and hexagonal scaffolds of 55% and 70% porosity [5]. Also effort has been done using as a bulk or either a matrix polycaprolactone (PCL) [8], [9] as PCL is a proper candidate for tissue regeneration, due to its' high mechanical properties [10]. Recently, it has been found that it has a good match with the heart's electrical conductivity [9].…”
Section: Introductionmentioning
confidence: 99%